Systemic Expression Analysis Reveals Prognostic Significance of WIPI3 in Hepatocellular Carcinoma - Liang, Tao-tao; Shao, Qi; Deng, Zhi-chao; Wang, Ting; Kang, Qiao-zhen (Frontiers in Genetics, 2020)
Introduction: WD repeat domain phosphoinositide-interacting protein 3 (WIPI3) is a member of WIPI protein family, autophagy marker, that is associated with the malignant progression of various human cancers, but its role in hepatocellular carcinoma (HCC) is still unclear. Materials and Methods: Firstly, we collected the mRNA expression of WIPI3 in HCC through the platform of Oncomine, as well as the DNA copy number variation (CNVs), and verified it on human HCC cell line and GEO database. Then, the sub-groups and prognosis of HCC were performed by UALCAN web-tool. The mutation of WIPI3 were analyzed by c-Bioportal. The co-expression of WIPI3 in HCC were identified from LinkedOmics database, and function enrichment analysis was used by LinkFinder module in LinkedOmics. Co-expression gene network was constructed through the STRING database, and the MCODE plug-in of which was used to build the gene modules, both of them were visualized by Cytoscape software. Finally, the top modular genes in the same patient cohort were constructed through data mining in TCGA LIHC by using the UCSC Xena browser. Results: The results indicated that WIPI3 was frequently overexpressed in HCC, which could lead to a poor prognosis through the Kaplan-Meier (KM) analysis. Moreover, there existed mutations of WIPI3 in HCC, and the prognosis of WIPI3 altered group was significantly poor based on KM plotter data. Co-expression analysis showed that the co-expression gene of WIPI3 was associated with cell cycle and spliceosome. Further analysis suggested that WIPI3 and eukaryotic translation initiation factor 4A3 (EIF4A3) coordinately regulated the cancer cell cycle by spliceosome as a result of the strong positive correlation between them. Conclusion: In summary, WIPI3 is constantly overexpressed in HCC tissues, resulting in a poor prognosis, therefore, we can identify it as an effective target for the treatment of HCC.